Human papillomavirus, sexually transmitted infections, and antimicrobial resistance in West Africa: Estimating population burden and understanding exposures to accelerate vaccine impact and drive new interventions: The PHASE survey protocol - Adedapo Olufemi Bashorun; Larry Kotei; Abdoulie F. Jallow; Ousubie Jawla; Emmanuel U. Richard-Ugwuadu; Muhammed Jagana; Lamin Bah; Amadou Tijan Bah; Karamo Conteh; Mamadou S.K. Jallow; Mehrab Karim; Bai Lamin Dondeh; et al. (PLoS ONE, 2025)
Human papillomavirus (HPV) infection is a primary cause of preventable deaths from cervical cancer, a condition of profound inequality with approximately 90% of deaths occurring in low- and middle-income countries, particularly in sub-Saharan Africa. In May 2018, the WHO Director-General declared a Joint Global Commitment to Cervical Cancer Elimination, highlighting the critical role of HPV vaccines in achieving this goal. However, there is a lack of systemically collected data on HPV prevalence in The Gambia, and impact data from high-income countries may not be reliably extrapolated to West African settings due to geographical variation in HPV types and distinct behavioural, biological, and sociodemographic exposures. The Gambia introduced a two-dose HPV vaccination schedule in 2019, but coverage has been very low, interrupted mainly by the COVID-19 pandemic. This presents a key opportunity to generate vital baseline data on HPV prevalence in the population before potential scale-up of vaccination efforts. The PHASE survey, a multi-stage cluster survey, aims to establish the baseline, population prevalence estimates of high-risk and low-risk, vaccine-type and non-vaccine-type HPV infection in 15- to 49-year-old females in The Gambia by measuring urinary HPV-DNA. The survey will also quantify the effects of various exposures on HPV prevalence, including sexual behaviour, the presence of other sexually-transmitted infections (STIs) - Neisseria gonorrhoea (NG), Chlamydia trachomatis (CT), Trichomonas vaginalis (TV), Mycoplasma genitalium (MG), syphilis, as well as blood borne viruses, human immunodeficiency virus (HIV), hepatitis B and hepatitis C; obstetric history, socio-demographic characteristics, and cervical cancer screening and/or treatment. Additionally, the study will provide important antimicrobial resistance (AMR) data for NG and MG in sub-Saharan Africa, a region poorly represented in global surveillance programs. This data is needed to guide regional treatment guidelines and advocate for new solutions, including gonococcal vaccines. The AMR data are expected to immediately influence recommendations regarding the appropriate choice of antibiotics for syndromic STI management in West Africa and hence to address an important driver of AMR in the sub-region. Leveraging on the Medical Research Council Unit The Gambia funded Health Demographic Surveillance system (HDSS) as its sampling frame, the survey will utilize validated diagnostic assays and culturally sensitive data collection methods, to ensure both scientific rigor and local relevance. Tools such as Audio Computer-Assisted Self-Interviewing (ACASI) technology, developed in consultation with local community advisory boards, are included to reduce social desirability bias in reporting sexual behaviour. This approach aims to maximize both the reliability and cultural appropriateness of the findings. This study directly addresses the critical need for baseline epidemiological data on HPV in a West African setting to accelerate vaccine impact and drive new interventions towards cervical cancer elimination. By understanding other factors that influence HPV (like other STIs, sexual behaviour, etc.), the study aims to ensure that, when the vaccine’s impact is measured later, changes in other confounding factors that may impact on HPV prevalence can be accounted for. The study will also establish the population prevalence of the measured STIs and their relationship to common symptoms and other adverse health outcomes related to STIs.